Effect of organic matter on strength development of self-compacting earth-based construction stabilized with cement-based composites. (1st October 2016) - Ma, Cong; Chen, Bing; Chen, Longzhu
Highlights: The effect of organic matter on the strength development of self-compacting poured earth is quantitatively evaluated. The mathematical models for predicting the compressive strength are proposed and their precision is verified. The influence of organic matter on phase changes of stabilized specimens is confirmed by XRD and SEM-EDS. Abstract: As an environmentally-friendly construction technique, modern rammed earth stabilized with Portland cement has attracted growing interest recently. Some organic clays with high water content are used to prepare self-compacting poured earth in South China. In this study, cement-based composites (CSCN) were employed to substitute Portland cement, and the influence of organic matter (humic acid powder, HAP) on strength development of self-compacting poured earth was investigated using reconstituted organic clay by unconfined compressive strength (UCS) test, X-ray diffraction (XRD) and scanning electron microscope (SEM). Due to the reduction of hydration products by adding HAP, the contribution of HAP was regarded as the consumption of CSCN and the quantitative analysis of consumption effect defined as consumption index ( OCI ) was investigated by the clay-water/CSCN ratio hypothesis. The interrelationship of OCI to curing time and the mathematical models for predicting the compressive strength of CSCN stabilized self-compacting poured earth with any HAP content were proposed. It was observed that the OCI values decreased with the increase of CSCN content and curing time. The precisions of consumption index and strength prediction models were verified by comparing predicted results and experimental results, and their deviation was mostly within 10%. The influence of HAP on phase changes in stabilized self-compacting poured earth was confirmed by XRD and SEM-EDS analysis, and the amounts of hydration products decreased significantly as increasing the HAP content.